Effects of duty ratio on properties of micro-arc film on Ti–3Zr–2Sn–3Mo–25Nb. (3rd September 2018) - Yang, Mei; Huang, Tingyu; Wang, Dan; Liu, Wei; Liu, Yang; Yang, Honglang; Yu, Sen
ABSTRACT: Porous titanium oxide layers, which are important features for improving the biological activity of Ti implants with bone tissues, have been obtained through the technique of micro-arc oxidation (MAO). Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to evaluate the micromorphology and crystalline structure of these oxide films, and the chemical compositions were measured by electron dispersive X-ray spectroscopy (EDS). TiO2 layers presented the crystalline phases of rutile and anatase. During the micro-arc oxidation treatment, Ca and P ions were incorporated into the oxide layer, and incorporation of Ca and P with the Ca/P content (%) of around 1.38 is similar to that in the human body. Nb2 O5 was also identified in the treatment samples. The corrosion resistance was evaluated using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarisation curves. In the electrochemical corrosion tests, the treated samples presented lower values of corrosion current density than untreated Ti, indicating a better corrosion resistance. Diffusion phenomena were present in the process of corrosion.